2021
DOI: 10.25259/cjhs_53_2020
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and satisfaction with antenatal care services among pregnant women in Lagos state, Nigeria

Abstract: Objectives: Despite the growing interest and efforts by government to make popular use of antenatal care (ANC) services in Nigeria as recommended by the World Health Organization, high level of infant and maternal mortality remains a major public health challenge facing the country. Dissatisfaction toward ANC services among pregnant women may be attributed to low level of awareness. This study assessed the level of awareness and satisfaction of ANC services among pregnant women in Lagos state, Nigeria. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The advent of urbanization and globalization has meant that non-traditional foods now dominate in most of the urban areas of West Africa and even in rural areas, the loss of work their food habits, they are influenced by the parents, friends, family, and media in their choice of food and eating habits. Also, they need nutritious and healthy foods and snacks at that age as they eat in a frequency of about 4 to 5 times a day [14]. Reports have demonstrated that children who skip breakfast have poor performance as they are likely to be inattentive, irritable, and lethargic in school [15].…”
Section: Food Intake and Dietary Habits Among Different Age Groups In...mentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of urbanization and globalization has meant that non-traditional foods now dominate in most of the urban areas of West Africa and even in rural areas, the loss of work their food habits, they are influenced by the parents, friends, family, and media in their choice of food and eating habits. Also, they need nutritious and healthy foods and snacks at that age as they eat in a frequency of about 4 to 5 times a day [14]. Reports have demonstrated that children who skip breakfast have poor performance as they are likely to be inattentive, irritable, and lethargic in school [15].…”
Section: Food Intake and Dietary Habits Among Different Age Groups In...mentioning
confidence: 99%
“…However, the calorie intake should be controlled so that it will not become excessive and thus lead to obesity. Therefore it is recommended that the diet of school-age children should consist of about 50-60% carbohydrate, 25-35% fats, and 10-15% protein [14]. In another report, gender was reported to have a significant effect on the eating habits of school-age children as boys are found to be less responsive to food than girls (that is boys are emotional eaters, they tend to stick to food based on familiarity while girls are more liable to try new food products).…”
Section: Food Intake and Dietary Habits Among Different Age Groups In...mentioning
confidence: 99%